Analysis of the Implementation of Coretax-Based E-Bupot Unification in Fulfilling Article 23 Income Tax Obligations at PT Karya Machindo Industries - Dhia Safinatunnajah; Asrofi Langgeng Noerman Syah; Dewi Kartika (Darul Yasin Al Sys, 2026)
The digital transformation of tax administration through the Coretax Administration System requires companies to adapt their compliance processes for withholding, issuing electronic withholding tax certificates, paying, and reporting Article 23 Income Tax. This study analyzes the implementation of Coretax-based E-Bupot Unification in fulfilling Article 23 Income Tax obligations at PT Karya Machindo Industries. A descriptive qualitative approach was employed, with data collected through observations, interviews, and documentation and analyzed through data reduction, data display, and conclusion drawing. The findings indicate that the implementation of Coretax-based E-Bupot Unification generally complies with applicable tax regulations and improves administrative efficiency. However, its implementation remains constrained by unclear descriptions of transaction objects on invoices, limited human resources, and system disruptions that may compromise the accuracy of tax withholding. The study concludes that Coretax facilitates the fulfillment of Article 23 Income Tax obligations, although its effectiveness depends on stronger transaction-identification and verification procedures. These findings contribute practical evidence regarding corporate adaptation to digital tax administration and underscore the need for companies to verify taxable transaction objects carefully before entering data into the Coretax system.